Metabolic syndrome and total cancer mortality in the Third National Health and Nutrition Examination Survey - Gathirua-Mwangi, Wambui G.; Monahan, Patrick O.; Murage, Mwangi J.; Zhang, Jianjun (Cancer causes & control, 2017)
Purpose Although metabolic syndrome incidence has substantially increased during the last few decades, it largely remains unclear whether this metabolic disorder is associated with total cancer mortality. The present study was carried out to investigate this important question. Methods A total of 687 cancer deaths were identified from 14,916 participants in the third National Health and Nutrition Examination Survey by linking them to the National Death Index database through December 31, 2006. Cox proportional hazards regression was performed to calculate hazard ratios (HR) and 95% confidence intervals (CI) for total cancer mortality in relation to metabolic syndrome and its individual components. Results After adjustment for confounders, a diagnosis of metabolic syndrome was associated with 33% elevated total cancer mortality. Compared with individuals without metabolic syndrome, those with 3, 4 and 5 abnormal components had HRs (95% CIs) of 1.28 (1.03–1.59), 1.24 (0.96–1.60), and 1.87 (1.34–2.63), respectively ( p -trend = 0.0003). Systolic blood pressure and serum glucose were associated with an increased risk of death from total cancer [HR (95% CI) for highest vs. lowest quartiles: 1.67 (1.19–2.33), p -trend = 0.002 and 1.34 (1.04–1.74), p -trend = 0.003, respectively]. Overall null results were obtained for lung cancer mortality. The effects of metabolic syndrome and its components on non-lung cancer mortality were generally similar to, but somewhat larger than, those for total cancer mortality. Conclusion Our study is among the first to reveal that metabolic syndrome is associated with increased total cancer mortality.